Effectiveness of the Go4Fun program: a comparison of face-to-face and digital delivery - Bronwyn McGill; Christian Young; NSW Health, Centre for Population Health Team†; Prevention Research Collaboration Team‡; Margaret Thomas (Sax Institute, 2024)
Objectives and importance of study: Despite an increasing trend in digitally delivered health promotion programs, evidence of their effectiveness compared to face-to-face approaches is limited. Go4Fun is a 10-week, scaled-up healthy lifestyle program in New South Wales (NSW) for children 7-13 years who are above a healthy weight and their families, delivered either face-to-face or digitally. We compared the impact of Standard Go4Fun (face-to-face) and Go4Fun Online (digital) on children's weight and health behaviour outcomes and whether attendance levels influenced outcomes. Study type: Pre-post study. Methods: We conducted a secondary analysis of Go4Fun cohort data from 1893 face-to-face and 1283 digital participants (January 2018 to May 2022). Outcomes of interest were body mass index z-score (zBMI), physical activity, sedentary behaviour, and fruit, vegetable, sugary drink and takeaway food consumption. Results: A higher proportion of Standard Go4Fun children lived in major cities, in areas of greatest disadvantage and spoke a language other than English at home than in Go4Fun Online. Children in both Standard Go4Fun and Go4Fun Online demonstrated improvements in all outcomes; however, children in Go4Fun Online showed significantly larger improvements. On average, digital participants had a reduction in zBMI of 0.11 more than the reduction seen in face-to-face participants (95% Confidence Interval [CI] -0.12, -0.09), increased the days/week of moderate-to-vigorous-physical-activity by 30% more (95% CI 24%, 36%), were more likely to eat ≥ 2 serves of fruit/day (compared to < 2, Odds Ratio [OR] 1.85; 95% CI: 1.36, 2.52) or eat ≥ 3 serves of vegetables/day (compared to < 3, OR 1.96; CI: 1.58, 2.42). Across both modes, with each additional session attended, the odds of eating ≥ 3 serves of vegetables/day increased by 10% (95% CI 1.02, 1.19). There were no significant differences for other health outcomes. Conclusions: Our evaluation demonstrated that both face-to-face and digital program delivery helped children above a healthy weight to improve their weight and health behaviour outcomes. Go4Fun Online achieved significantly greater improvements in outcomes, which is encouraging for the future of digital interventions. Participation in Standard Go4Fun by more children with obesity from disadvantaged areas and non-English speaking backgrounds suggests that ongoing delivery of both modes of Go4Fun could facilitate program reach among all children above a healthy weight.